The Social Dimensions of Creativepreneurship Education: Unleashing Youth’s Creative Potentials through Teamwork and Collaborative Creativity - Suryani, Adi; Soedarso, Soedarso; Windiani, Windiani; Hanoraga, Tony; Harmadi, Sonny Harry B.; Setyaningsih, Yuni (International Journal Pedagogy of Social Studies, 2022)
Young people are the hope of community. They are frequently expected to be dynamic, creative, innovative, positive and kind. As agents of change, they are expected to be generation who can empower community and make positive changes. Positive and healthy youth can be human investment. Thus, considerable concern on youth development needs to be heightened. One of many competencies which may empower both the youth and their communities is creativepreneurship skill. Numerous existing studies discuss how to teach business and individual development. Less concern is arisen to voice social learning needs of youth creativepreneurship. This study aims to fill the gap by bridging business-individual development approaches in creativepreneurship education to social learning. It intends to provide education for increasing youth competencies of Karang Taruna Karang Rejo Sawah, Wonokromo, Surabaya. The study adopts qualitative method by utilizing direct observation and authors’ natural role in observation as mentors. The study shows that youth creativepreneurship education can be enhanced by social learning through social observation-modelling and teamwork creativity. Through observation-modelling, the youth can learn how to start business, tackle challenges from the expert models. They also can sense the happy and desperating emotion from the models’ stories, resiliencing and implementing effective strategies. Meanwhile, the teamwork creativity activities enable the youth to work and learn in teams, interpersonal communication, emotional and cognitive sharing, internal or self-emotion management and individual-team alignment.